Expert Opinions about Barriers and Facilitators to Physical Activity Participation in Ghanaian Adults with Type 2 Diabetes: A Qualitative Descriptive Study - Mohammed Amin; Debra Kerr; Yacoba Atiase; Yusif Yakub; Andrea Driscoll (Sports, 2023)
Most adults with type 2 diabetes mellitus (T2DM) do not meet their physical activity (PA) goals despite its importance in improving their health outcomes. Our study aim was to explore the opinions of healthcare professionals regarding barriers and facilitators to PA participation in Ghanaian adults with T2DM. Using qualitative descriptive design, data were collected through semi-structured interviews with 13 healthcare professionals experienced in diabetes management in Ghana. Three main themes relating to PA barriers and facilitators were identified in a thematic analysis: health system-related factors, healthcare practitioner factors, and patient factors. Inadequate accessibility to physical therapists and therapy centres hindered the provision of PA programs. Nurses and doctors lacked sufficient knowledge and training on effective PA interventions for individuals with T2DM. Time constraints during patient consultations limited discussions on PA, while the cost associated with accessing physical therapy posed a significant challenge. Patients often disregarded PA advice from physical therapists due to their reliance on doctors, and some perceived PA as irrelevant for diabetes treatment. Despite these barriers, healthcare professionals expressed belief in PA facilitators, including integrating physical therapists and diabetes educators into diabetes care, providing structured exercise resources, improving curriculum planning to emphasise PA in health science education, and addressing knowledge gaps and misconceptions. Overall, this study highlights patient-related and healthcare system-related factors that influence PA behaviour in Ghanaian adults with T2DM. Findings from this study should inform the development of tailored PA programs for this population.